Molecular Mechanism of Diaminomaleonitrile to Diaminofumaronitrile Photoisomerization: An Intermediate Step in the Prebiotic Formation of Purine Nucleobases. Issue 9 (27th January 2014) - Szabla, Rafał; Góra, Robert W.; Šponer, Jiří; Šponer, Judit E.
Abstract The photoinduced isomerization of diaminomaleonitrile (DAMN) to diaminofumaronitrile (DAFN) was suggested to play a key role in the prebiotically plausible formation of purine nucleobases and nucleotides. In this work we analyze two competitive photoisomerization mechanisms on the basis of state‐of‐the‐art quantum‐chemical calculations. Even though it was suggested that this process might occur on the triplet potential‐energy surface, our results indicate that the singlet reaction channel should not be disregarded either. In fact, the peaked topography of the S1/S0 conical intersection suggests that the deexcitation should most likely occur on a sub‐picosecond timescale and the singlet photoisomerization mechanism might effectively compete even with a very efficient intersystem crossing. Such a scenario is further supported by the relatively small spin–orbit coupling of the S1 and T2 states in the Franck–Condon region, which does not indicate a very effective triplet bypass for this photoreaction. Therefore, we conclude that the triplet reaction channel in DAMN might not be as prominent as was previously thought.